Pengembangan dan Peningkatan Profesionalisasi Kependidikan di Lembaga Pendidikan Islam - Nuril Qodri Mubarok; Ilhamus Subhaniyah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
One of the educational innovations that is needed today is to develop the professionalism of education personnel. This is done in an effort to improve the quality of educational services in schools/madrasahs in order to improve the quality of education. So this scientific paper was written to explain the development and improvement of educational professionalization in the Madrasah Ibtidaiyah At-Taqwa Bondowoso institution. As we know that in an institution the name of development and improvement of education is needed to get professional educators. This is done to get superior student results in the eyes of the world. The purpose of education has two functions, namely to provide direction to all educational activities and is something that all educational activities want to achieve. This research method Departs from the background above, this study aims to determine the extent of efforts made by educational institutions in developing and improving the professionalism of education personnel. This study used qualitative research. The data collection techniques are in the form of observation and interviews. Then the data obtained are analyzed using the description and analysis method with an inductive mindset pattern. Educational professionalism is very influential on students. The success or failure of students in learning, one of which can be seen from the professionalism of the educator